Study of tritium transport characteristics in a transportable fluoride‐salt‐cooled high‐temperature reactor. (11th December 2017) - Qin, Hao; Wang, Chenglong; Qiu, Suizheng; Zhang, Dalin; Tian, Wenxi; Su, G. H.
Summary: Tritium management is one of the most critical issues that limit the development of fluoride‐salt‐cooled high‐temperature reactor (FHR); therefore, it is important to figure out the tritium transport characteristics in FHRs. In this paper, 3 works concerning about tritium in FHR are conducted: first, the tritium transport characteristics in the primary loop of FHRs are introduced, including tritium production and speciation, the absorption and desorption by graphite, dissolution and diffusion in molten salt, and permeation through structural materials. Second, the physical and mathematical models are established for tritium transport characteristic analysis in a transportable FHR (TFHR). The tritium transport characteristic analysis code (TAPAS) for TFHR is developed and benchmarked. The results prove the fidelity and accuracy of TAPAS. Finally, the tritium transport characteristics in the TFHR are analyzed systematically by TAPAS. Three conclusions are obtained: (1) tritium in the primary coolant loop is mainly in the form of T2 ; (2) when TFHR operates at steady state, the permeation rate of T2 can be regarded as a constant (9.03 × 10 9  Bq ⋅ EFPD −1 ); and (3) 7 Li enrichment and redox potential of molten salt have great influence on the tritium distribution. This work might provide contribution to the tritium control in FHRs. Abstract : The tritium behaviors in the FHRs are introduced in detail. The tritium transport characteristic analysis code (TAPAS) for FHR is developed and benchmarked. The tritium transport characteristics in the TFHR are analyzed systematically, and some methods for tritium mitigation are evaluated.